Mandatory Check for COPMI in Adult Mental Healthcare Services in the Netherlands—A Quantitative and Qualitative Evaluation - Everts, Saskia; van Amelsvoort, Therese; Leijdesdorff, Sophie (Frontiers in Psychiatry, 2022)
Background Children of parents with a mental disorder and/or addiction (COPMI) are at increased risk of developing a mental disorder. In spite of preventive interventions that can decrease the risk of problem development, COPMI are not automatically offered help. In 2013, a mandatory COPMI check was implemented in the Netherlands, requiring every mental health care professional to check whether their adult patients have children and to assess these children's safety and needs. Earlier research has shown that a gap between these regulations and the actual integration in clinical practice is not uncommon. Method In the current study, we evaluated the implementation of the mandatory COPMI check in the Netherlands, using quantitative as well as qualitative data from a large mental healthcare organization in the Netherlands that offers both Child and Adolescent Mental Health and Adult Mental Healthcare. Results Files from 14,469 patients were analyzed quantitatively and a sample of 150 files was further analyzed in depth. Findings were refined through 4 focus groups with adult mental healthcare professionals. It was found that while there are examples of the tool leading to interventions for COPMI, the tool is often not used, and when used tends to direct the focus away from COPMI needs and organizing help toward the more narrow and problematic focus on safety and reporting to child abuse authorities. Conclusion The potential of the COPMI check is currently not fully realized. Strategies to improve its effectiveness in clinical practice are needed to improve access to interventions for COPMI.